The role of cooperatives in democratization and development A case of Uson Small Coconut Farmers Multi-Purpose Cooperative. - Coton, Vennie G. (Tacloban City Vennie G. Coton, 2009)
The study wants to know how cooperative contribute to the economic development and how it facilitate the democratization process. The focus of this study is the Uson Small Coconut Farmers Multi-Purpose Coopeative or USCOFAMCO.
The Uson Small Coconut Farmers Multi-Purpose Cooperative was established in 1991 and was registered at the Cooperative Development Authority on October 29, 1992. It was registered at CDA in registration number TAC-179. The coop is situated at Brgy. Uson Caibiran, Biliran. Barangay Uson is located at the southern portion of the Municipality of Caibiran. Most of the people living in the area were farmers and fisherman.
In conducting this study, I designed an interview schedule which sought to determine how the cooperative serve as a vehicle for rural development and on how it goes into the democratization process. The persons that I have interviewed in particular were the members of the cooperatives, the management and the member of the Board of Directors who has the power to decide on matters pertaining to the operation of the cooperative.
The organization of the coop was a member's initiative. With its more than 15 years of existence, I could say that USCOFAMCO contributed to the development of the community. The coop existence for a long period of time as well as its fastly growing asset could be attributed to the good management as well as the commitment of the members to its programs and activities.
The cooperative provided development to the community through the services that it offers. USCOFAMCO provide transport services for its members. It also renders financial assistance to a qualified son/daughter of the member who is studying through the scholarship program. In addition, a cash incentive is to be given to an employee who is about to retire. In case of the death of the member, the coop give certain amount to the family. Not only that, the cooperative also aided the barangay council in the development project just like the water system.
To enhance local production, the USCOFAMCO allows each member to have loans. USCOFAMCO provides employment opportunities for the people just like the being a "tindera", delivery boy, panadero, drivers, laborers in the copra trading, the treasurer and the book keeper.
The cooperative operates democratically. All the members have the opportunity to decide on all matters concerning the operation of the coop. This usually happens during the general assembly. In the general assembly, many issues were discussed. Issues being discussed ranges from those that affect the operation of the coop, the members itself and the community where the coop is located. As a democratic institution, USCOFAMCO encouraged local participation in the decision making process. The coop has already extended a lot of services that were beneficial to the members even to the non-members.
Undergraduate thesis (B.A.S.S. Political Science)--University of the Philippines, Tacloban
Keywords: Social Science